Investigating students' perspectives on the utilization of mobile-assisted language learning and mobile games for developing speaking proficiencies - Aditya, Apta Rahadi; Kalisa, Pasca (ELT Forum: Journal of English Language Teaching, 2025)
For English as a Foreign Language (EFL) learners, speaking is a skill that poses significant challenges, primarily due to insufficient practice, low self-esteem, and limited conversational opportunities. Mobile-Assisted Language Learning (MALL) and mobile gaming offer creative and engaging ways to enhance speaking abilities in the current digital learning environment. This qualitative study examines how students perceive the impact of mobile games on enhancing their English-speaking skills. Ten undergraduate EFL students, ages 20 to 23, who had studied English for six to ten years and frequently played mobile games, participated in semi-structured interviews to gather data. According to a thematic study, mobile games increased learners’ motivation, improved pronunciation, helped them acquire new vocabulary, and gave them more confidence when speaking. Participants observed that the interactive elements of games reduced speaking anxiety and promoted real-world conversational practice. However, difficulties remained, such as comprehending rapid-fire discourse and navigating new colloquialisms. The study shows that the deliberate integration of mobile apps can augment conventional classroom techniques and promote organic spoken language development.